Spatial distribution and analysis of soil loss over micro watersheds of Sierra de Vaqueros (Salta, Argentina) by using a GIS - Moreno, Ramona Ignacia (2017)
Immediately north of Salta city, several streams have their sources on the eastern slopes of the Sierra de Vaqueros, whose piedemonte is urbanized. The man influence on the mountain environment makes it necessary to estimate erosion rates the location of their different erosion classes and their analysis. The work was carried out with satellite images, generating the base map and thematic maps of the Vaqueros and Los Nogales microbasins, through the use of a Geographic Information System (GIS); this allowed to characterize the study areas and to obtain the necessary information to apply the Universal Equation of Soil Loss (USLE). R, K and LS factors were obtained through adaptations of the method, due to the unavailability of data established by authors. The average of current water erosion showed a rate of 47 t/ha/year for the Vaqueros microbasin and 45 t/ha/year for the microbasin Los Nogales. The different categories of erosion were located and analyzed considering the interaction of the acting factors. For the achievement of a better environmental quality simple measures to influence the possible factors to be modified were proposed.